Chemical Composition, In Silico Investigations and Evaluation of Antifungal, Antibacterial, Insecticidal and Repellent Activities of Eucalyptus camaldulensis Dehn. Leaf Essential Oil from ALGERIA - Ghozlane Barboucha; Noureddine Rahim; Houssem Boulebd; Amina Bramki; Anna Andolfi; Maria Michela Salvatore; Marco Masi (Plants)
This study investigated the phytochemical profile and evaluated the antimicrobial and insecticidal properties of Eucalyptus camaldulensis Dehn. essential oil (EC-EO) from Algeria, using in vitro and in silico approaches. The yield of EC-EO was 0.27%, with gas chromatography-mass spectrometry (GC-MS) revealing spathulenol (58.24%), cryptone (17.22%), and o-cymene (15.53%) as the major compounds. EC-EO exhibited notable antibacterial activity, particularly against Salmonella typhimurium (14 ± 1.00 mm) and Staphylococcus aureus (14.5 ± 0.50 mm). It also showed effective antifungal activity against Penicillium sp. (11.5 ± 0.49 mm), Candida albicans (11.2 ± 0.29 mm), and Aspergillus fumigatus (9.8 ± 0.27 mm). Insecticidal assays against Tribolium castaneum were conducted using contact toxicity, fumigation toxicity, and repellent activity methods. The median lethal concentration (LC50) for contact toxicity was 0.011 μL/insect after 72 h, while the fumigation test had an LC50 of 122.29 μL/L air. Repellent activity tests showed percentage repellency (PR) values exceeding 80% after 6 h. The molecular geometry and electronic properties of the main compounds were studied using density functional theory (DFT) calculations. In addition, the interaction mode and binding affinity of these molecules with three key enzymes involved in antimicrobial activity, DNA gyrase, dihydrofolate reductase (DHFR) and Tyrosyl-tRNA synthetase (TyrRS), were explored by molecular docking.